Uji Aktivitas Antimikroba Ekstrak Kunci Pepet (Kaempferia Rotunda L.) - Dina Trianggaluh Fauziah (Jurnal Kesehatan dr. Soebandi, 2020)
Kunci Pepet Rhizome is a medicinal plant from ginger family which contains many secondary metabolites including essential oils, flavonoids and terpenoids, which can act as therapy for dysentery, diarrhea, and also for body slim treatment. The extraction method that was used in this research is fractionated solvent extraction using n-hexane, dichloromethane and ethanol. Those fractions were tested for its antimicrobial activities using agar diffusion method. Identification of the qualitative content of secondary metabolites is carried out by TLC. Inhibition zones of ethanol extract, n-hexane, dichloromethane and aqueous fraction against Escherichia coli, Staphylococcus aureus and Candida albicans were 2.08cm, 1.37cm, 1.47cm, 1.27cm, 2.13cm, 1.30cm, 1.30cm, 1.57cm, 1.82cm, 1.27cm, 1.50cm, 1.33cm, respectively. The inhibition zones of the crude extract, fractions of n-hexane, dichloromethane and aqueous fraction are 1.82cm, 1,27cm, 1.50cm, 1.33cm. GCMS analysis of the extract showed that it contains contains benzoic acid (8.97%), hexadecane (28.84% and 33.50%), benzyl benzoate (89.21%, 14.71%, 7.23% and 19.88%), 2-hydroxy benzoic acid ester phenilmethil (0.90%), heksadekanoat acid (0.92%, 10.10%, 7.04% and 11.71%), benzyl alcohol (12.30%), pentadekana (7.22%), octadecanoic methyl ester (5.43%).